Improving Islamic Education Learning Outcomes of Fifth Grade Students of SD Negeri 03 Minas Barat Using the Demonstration Method - Hertati, Hertati; Dewi, Sinta; Rainelda, Rainelda (STKIP Rokania Pasir Pangaraian, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) of grade V students of SD Negeri 03 Minas Barat through the application of the demonstration method. The type of research used was Classroom Action Research (PTK) with a subject of 39 students. This research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through learning outcome tests, observations, and interviews. The results showed an increase in student learning outcomes after the application of the demonstration method. In cycle I, the average student score reached 72 with a completion percentage of 64.1%, while in cycle II it increased to 85 with a completion percentage of 89.7%. Thus, the demonstration method proved effective in improving students' PAI learning outcomes.